2018
DOI: 10.4048/jbc.2018.21.e35
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Prediction of Breast Cancer Survival Using Lymph Node Ratio

Abstract: PurposePrevious oncological studies showed that lymph node ratio (LNR) (ratio of number of lymph nodes that tested positive for metastasis to the total number of lymph nodes examined) is a negative indicator of cancer survival. The American Joint Committee on Cancer (AJCC) staging system incorporates tumor size, lymph node involvement, and metastasis in a comprehensive model of cancer progression, but LNR alone has been shown to outperform the AJCC system in prognostic and survival predictions for various type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…LNR is defined as the ratio between LNs with metastasis versus the total number of LNs retrieved, and thus does not solely rely on positive LNs. Several studies have shown that LNR has greater ability to predict the OS of patients compared with traditional TNM staging, and that LNR should be considered as an alternative to pN staging (2)(3)(4)(5)(6)(7)(8). The definition of pN =0 is equal to LN R =0, indicating no LNs with metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…LNR is defined as the ratio between LNs with metastasis versus the total number of LNs retrieved, and thus does not solely rely on positive LNs. Several studies have shown that LNR has greater ability to predict the OS of patients compared with traditional TNM staging, and that LNR should be considered as an alternative to pN staging (2)(3)(4)(5)(6)(7)(8). The definition of pN =0 is equal to LN R =0, indicating no LNs with metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Axillary lymph node status was of great clinical significance in BC prognosis. 31 The entropy parameter computed for BC thermal images was decreased in both breasts by 10% on average after RIMH.…”
Section: Resultsmentioning
confidence: 92%
“…Axillary lymph node status was of great clinical significance in BC prognosis. 31 The entropy parameter computed for BC thermal images was decreased in both breasts by 10% on average after RIMH. Color Doppler US examinations were recorded to assess blood flow in the breasts in the experimental group ( Figure 5).…”
Section: Patientsmentioning
confidence: 92%
“…Therefore, it can imply that survival was decreased while number of nodes metastasis was increased. Hung et al, (2018) revealed that lymph node ratio was a proper prognosis factor of survival than TNM system from the American Joint Committee on Cancer (AJCC).…”
Section: Discussionmentioning
confidence: 99%